2019
DOI: 10.3390/nano9010076
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Fast Method to Synthesize Cubic Iridium Nanoparticles with Clean Surface Free from Surfactants

Abstract: Cubic Iridium nanoparticles without any surfactants on the surface have been synthesized successfully in this work. The process of synthesis was quite simple by just injecting one drop of 400 µL solution containing Iridium precursor onto Cu foil (1 cm × 1 cm), and through galvanic reaction between the Ir precursor and Cu foil, the cubic Iridium nanoparticle could be obtained quite quickly (<30 s). The Cu foil played the roles of both reducing agent and substrate. This method could also be employed to synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…33 Cubic iridium nanoparticles without any surfactants on the surface can be synthesized at room temperature by the galvanic replacement reaction. 34 For this purpose, a drop of an aqueous solution containing a proper amount of IrCl 3 and CuCl 2 has been injected on a Cu foil. The size of the formed Ir nanocubes varies from 120 to 200 nm with the average edge length of 158 nm.…”
Section: Iridium Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Cubic iridium nanoparticles without any surfactants on the surface can be synthesized at room temperature by the galvanic replacement reaction. 34 For this purpose, a drop of an aqueous solution containing a proper amount of IrCl 3 and CuCl 2 has been injected on a Cu foil. The size of the formed Ir nanocubes varies from 120 to 200 nm with the average edge length of 158 nm.…”
Section: Iridium Nanoparticlesmentioning
confidence: 99%
“…The size of the formed Ir nanocubes varies from 120 to 200 nm with the average edge length of 158 nm. 34 Nanoparticles with well-dened iridium crystal facets can be obtained, for example, by the deposition of iridium layer on some regular palladium nanoparticles. 35 Using cubic and octahedral Pd nanoparticles encased by {100} and {111} facets, respectively, as the seeds, it is possible to generate Pd@Ir cubic and octahedral nanoparticles with Ir{100} and Ir{111} facets.…”
Section: Iridium Nanoparticlesmentioning
confidence: 99%
“…In addition, no universal method has been found to remove surfactants in different synthesis methods which employed different surfactants . Another strategy to synthesize shaped nanocatalysts with a clean surface is to avoid introducing any surfactants during the process of synthesis; thus, it can guarantee the cleanness of the shaped nanocatalysts as synthesized. A representative work of the second strategy was the successful synthesis of tetrahexahedral platinum NCs enclosed with (730) high index facets using the square-wave potential (SWP) electrodeposition method . In this method, they employed no surfactants, and the shape-controlled synthesis was achieved just by repeated oxygen adsorption and desorption on the surface or subsurface of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the morphology of the particles was temperature dependent, with the films deposited at lower temperatures comprising of an agglomeration of spherically shaped nanoparticles while the films deposited at a higher substrate temperature were composed mainly of cubic shaped nanoparticles. The formation of nanocubes is due to preferential crystal plane orientation over others during the growth of the films [76,77]. These variations in the particle morphologies resulted in a significant variation of the shapes of the photoluminescence (PL) spectra depicted in the 13th figure.…”
Section: Structure Morphologies and Luminescence Of Thin Films Deposited Using Pldmentioning
confidence: 99%